The beck anxiety inventory for Malays (BAI-Malay): a preliminary study on psychometric properties - Mukhtar, Firdaus; Zulkefly, Nor Sheereen (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Introduction: The purpose of the present study was to investigate exploratory factor analysis of the Beck Anxiety Inventory (BAI) and reports its reliability and validity in Malaysia. Method: One thousand and ninety participants from four different samples(namely students, general population, medical and psychiatric patients) completed the Malay version of Beck Anxiety Inventory, as well as additional questionnaires such as Fear Questionnaire, Anxiety Sensitivity Index, Depression Anxiety Stress Scale, and Catastrophic Cognition Questionnaire. Results: Exploratory factor analysis revealed a three factor solution and accounted for 48.01% of the total variance. The three-factor structure appeared to be; subjective anxiety, autonomic, and neurophysiology. The Cronbach alpha coefficients (α) ranged from 0.66 to 0.89 with satisfactory overall alpha value (.91). Evidence was also found acceptable concurrent validity of the BAI-Malay (range between r=.22 to r=.67). Conclusion: This study shows that the BAIMalay is a reliable and valid instrument to measure symptoms of anxiety in the Malay population and can be used in research and clinical service in Malaysia. However, replication of study by using confirmatory factor analysis and application of the instrument among anxiety patients worth of further investigation.